2023
DOI: 10.1177/02697580231154941
|View full text |Cite
|
Sign up to set email alerts
|

Less exposed, more vulnerable? Understanding the sexual victimization of women with disabilities under the lens of victimological theories

Abstract: This study aims to examine the sexual victimization process of individuals with disabilities using the interactional victimology theoretical framework. Specifically, we compare the victimological indicators of four different situations: victims were not disabled, victims were physically disabled, victims were psychologically disabled, and finally, victims were both physically and psychologically disabled. The sample used in this study consists of 1,077 cases of extrafamilial sexual assaults involving adult vic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…At the same time, limited self-assertion will also make a person easier to persuade. In a recent study, Chopin et al (2023) described offenders as often being known to the disabled victim and using deception to approach their target, and their victims as being unlikely to resist. The above quotations are examples of people with intellectual disabilities quickly giving up on saying no, and, according to Snell et al (2009), this might be because they believe or agree to what someone says with little or no question.…”
Section: Biddable Despite Having Reservationsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, limited self-assertion will also make a person easier to persuade. In a recent study, Chopin et al (2023) described offenders as often being known to the disabled victim and using deception to approach their target, and their victims as being unlikely to resist. The above quotations are examples of people with intellectual disabilities quickly giving up on saying no, and, according to Snell et al (2009), this might be because they believe or agree to what someone says with little or no question.…”
Section: Biddable Despite Having Reservationsmentioning
confidence: 99%
“…Intellectual disabilities or impaired or reduced social skills, such as understanding how to act or defend oneself in potentially abusive situations, are associated with an increased risk of abuse (Hughes et al 2012;Nixon et al 2017). Dependence on others in the activities of daily life seems to increase legal vulnerability (Chopin et al 2023). Explaining the assumed vulnerability of people with intellectual disabilities by personal traits, however, dismisses the barriers that arise in the gap between society's demands and the person's abilities (Wehmeyer et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Even the definition of sexual homicide, put forth by the Federal Bureau of Investigation (FBI) and widely adopted by many researchers, includes criteria that centers the state of the victim: their attire or lack of attire, the sexual positioning of their body, exposure of their sexual parts, evidence of foreign object insertion, signs of sexual activity, and signs of substitute sexual activity (Ressler et al., 1992). More recent work has introduced the idea of centering the victim and using victimological theories to understand crime (e.g., Chai et al., 2023; Chopin et al., 2023; Deslauriers‐Varin & Beauregard, 2010). An analysis of SH victims in particular could help further the understanding of how these theories perform when applied to violent interpersonal crimes.…”
Section: Introductionmentioning
confidence: 99%
“…And finally, Chopin et al. (2023) examined the sexual victimization of women with disabilities through the lens of routine activities and lifestyle theories. The authors found that women with disabilities were more likely to experiences extreme forms of sexual victimization through excessive violence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation